A tradução dos símbolos de morte e de liberdade na adaptação audiovisual de Incidente em Antares, de Érico Veríssimo - Silva, Francisco Marcelino da (2023)
The present work focused on the analysis going from the source text Incidente em Antares by Érico Veríssimo to the TV series of the same name that was produced by Globo Television Company (1994) – the target text – more specifically it will be emphasized the symbols of Death and Freedom on our corpus because it would be unsustainable to do a wider analysis of our research object. Concerning Translation theoreticians, we will use the concepts developed by Jakobson (1969) about the different kinds of translation – intralingual, interlingual and intersemiotic; Plaza (2003) with his fundamental work and Stam (2000/2008) that leans towards the Adaption Studies in the audiovisual field, especially, to the cinema. On the studies about Death, we will follow the path made by the French historian Ariès (2014) because we believe to be worthy to understand the study of how is the relation between the living and the dead – bearing in mind that the corpus of our narrative investigates the resurrection of seven dead people and their conflicts with the citizens of Antares – and finally on the studies about Freedom, we seek to acknowledge better the individual, collective, social and political freedom, based on some Rousseau`s (2011) concepts, experienced by distinct social strata represented by the seven dead people: Quitéria Campolargo, Cícero Branco and Menandro Olinda representing the bourgeoisie; Barcelona (José Ruiz) and João Paz as part of the working class; and Pudim de Cachaça and Erotildes the social excluded ones. The connection established between the seven corpses with Death itself and with the lost and/or gain of Freedom will be common thread of our analysis, and also, of course the representation of them in the TV series.